Application of S transform for detection of external interferences in online transformer impulse frequency response analysis - Mohseni, B.; Hashemnia, N.; Islam, Syed (2017)
Online impulse frequency response analysis is a recently-developed diagnostic method for in service transformer with a promising outlook. This paper aims to detect the impact of external interferences including pulse shaped interferences from switching operations and other phenomena in the power system on the frequency response of the transformer. For modeling the transformer for online IFRA, a simulation approach based on finite element analysis (FEA) and circuit analysis is used. In this approach, instead of using a linear model with static parameters, 3D finite element model of the transformer is calculated in Maxwell Software and then exported into an external Maxwell Spice circuit which allows for study the terminal behaviors of the transformer. A modified S transform is then applied to the recorded input and output signals in healthy and faulty conditions to construct the electrical impedance as well as the time-frequency contours of the transient responses.